Two new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Paraguaçu basin, Chapada Diamantina, Bahia, Brazil - Zanata, Angela M.; Burger, Rafael; Camelier, Priscila (Zootaxa, 2018)
Astyanax lorien and A. rupestris are described from tributaries of upper rio Paraguaçu basin, Bahia, Brazil. Both species shares the majority of the characters currently used to define the Astyanax scabripinnis species complex, with highest body depth approximately at vertical through pectoral-fin midlength and a low number of branched anal-fin rays (15–21). Astyanax lorien is distinguished from its congeners by a combination of characters, including presence of small bony hooks on all fins of mature males, a unique vertically elongate humeral blotch, and ventral margin of the third infraorbital close to the horizontal limb of preopercle. Astyanax rupestris is distinguished from its congeners also by a combination of characters, including ventral margin of third infraorbital distinctly separated from horizontal limb of preopercle, leaving a broad area without superficial bones, absence of midlateral stripe on body, absence of blotch on caudal peduncle, and presence of a vertically elongated conspicuous dark humeral blotch, not bordered anteriorly and posteriorly by distinct unpigmented areas. Both species are apparently endemic to the upper portion of the Paraguaçu river basin, within the Chapada Diamantina domain.